Japanese antimicrobial consumption surveillance: First report on oral and parenteral antimicrobial consumption in Japan (2009–2013). (December 2016) - Muraki, Yuichi; Yagi, Tetsuya; Tsuji, Yasuhiro; Nishimura, Nobuhiro; Tanabe, Masaki; Niwa, Takashi; Watanabe, Tamayo; Fujimoto, Shuhei; Takayama, Kazuro; Murakami, Nobuo; Okuda, Masahiro
Highlights: First report regarding total antimicrobial consumption in Japan. Total antimicrobial consumption in Japan was less than in other countries. Higher volume of oral broad-spectrum antimicrobials has been consumed in Japan. Abstract: No reliable national antimicrobial consumption data have been available in Japan. The Japanese antimicrobial consumption surveillance (JACS) project started to collect data nationwide on antimicrobial consumption. This paper provides the first sales data from the JACS project on oral and parenteral antimicrobial consumption in Japan as well as the trends for the years from 2009 to 2013. The population-weighted total consumption was expressed as defined daily doses (DDDs) per 1000 inhabitants per day (DID). The value of DID increased from 14.7 in 2009 to 15.8 in 2013. Notably, oral antimicrobials accounted for 92.6% (mean of 2009, 2011 and 2013) of total consumption. Oral third-generation cephalosporins, macrolides and fluoroquinolones accounted for 77.1% (mean of 2009, 2011 and 2013) of oral consumption. Consumption of antimicrobials has increased during the years 2009 and 2013 regardless of the dosage form. This is the first report regarding the population-weighted consumption of oral and parenteral antimicrobials in Japan during the years 2009 and 2013. These results provide useful information for combating the menace of antimicrobial resistance in Japan.